2017
DOI: 10.1242/jcs.196758
|View full text |Cite
|
Sign up to set email alerts
|

Retromer- and WASH-dependent sorting of nutrient transporters requires a multivalent interaction network with ANKRD50

Abstract: Retromer and the associated actin-polymerizing WASH complex are essential for the endocytic recycling of a wide range of integral membrane proteins. A hereditary Parkinson's-disease-causing point mutation (D620N) in the retromer subunit VPS35 perturbs retromer's association with the WASH complex and also with the uncharacterized protein ankyrin-repeat-domain-containing protein 50 (ANKRD50). Here, we firmly establish ANKRD50 as a new and essential component of the SNX27-retromer-WASH super complex. Depletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 42 publications
5
56
0
Order By: Relevance
“…Importantly, SLC3A2 total protein levels were also downregulated in WASH and retromer knockout cells (Fig A and D). This latter finding is also in accordance with previous proteomic studies and argues for a common trafficking pathway essential for both SLC3A2 and Basigin sorting and requiring RAB21, WASH, and the retromer.…”
Section: Resultssupporting
confidence: 92%
“…Importantly, SLC3A2 total protein levels were also downregulated in WASH and retromer knockout cells (Fig A and D). This latter finding is also in accordance with previous proteomic studies and argues for a common trafficking pathway essential for both SLC3A2 and Basigin sorting and requiring RAB21, WASH, and the retromer.…”
Section: Resultssupporting
confidence: 92%
“…This was further confirmed by our RAB7 knockout and rescue experiments, which established that GTP‐locked RAB7 is fully competent in restoring retromer‐mediated recycling. We have just reported that the retrograde sorting of CI‐MPR does not depend on the retromer trimer; instead, we found even slightly faster delivery of CI‐MPR to the TGN in VPS35‐deficient cells (Kvainickas et al , a,b). It remains to be explored further whether the control of RAB7 activity is a modulating factor for the SNX‐BAR‐dependent transport of CI‐MPR that we observed.…”
Section: Discussionmentioning
confidence: 63%
“…Loss of the retromer‐associated proteins VARP (Hesketh et al , ) and FAM21 (Gomez & Billadeau, ) led to a decrease in lysosomal RAB7, suggesting lower RAB7 activity (Fig A). We could not detect significant changes with the retromer and FAM21 binding proteins ANKRD50 (Kvainickas et al , b) and FKBP15 (Harbour et al , ). The same set of cells was also subjected to the GST‐RILP‐based RAB7 activity assay, which confirmed the results from the microscopy‐based screen, as loss of TBC1D5 and to a lesser extent SNX1/2 and VAMP7 led to an increase in RILP‐bound, active RAB7, whereas loss of FAM21 and VARP resulted in less active RAB7 that bound to the beads (Fig B).…”
Section: Resultsmentioning
confidence: 71%
“…FAM21 is comprised of a head domain (~220 amino acids), which is necessary to interact with other members of the WASH complex, and an extended C‐terminal tail containing 21 repeats of a novel acidic motif (L‐F‐[D/E] 3‐10 ‐L‐F), termed the LFa motif. The FAM21 tail has been suggested to function as an endosomal signaling hub recruiting numerous proteins, including the actin‐capping protein CapZ, ANKRD50, FKBP15, TBC1d23, RME‐8 and the CCC complex (Figure A).…”
Section: Wash Complexmentioning
confidence: 99%